Kajian Literatur tentang Pengaruh Logo Halal Terhadap Keputusan Pembelian Konsumen Muslim di UMKM - Fadhil Musyafa; Novien Rialdy (PRODUCTIVITY: Journal of Integrated Business, Management, and Accounting Research, 2024)
This study aims to analyze the influence of halal logos on consumer purchase decisions in MSMEs through a literature review approach. The halal logo is one of the important elements in building Muslim consumer trust and increasing the competitiveness of MSMEs in the local and global markets. This study collects and synthesizes various previous studies that discuss the relationship between halal logos, consumer perceptions, and purchasing decisions. Data collection is carried out through systematic searches in databases such as Google Scholar, with the keywords "halal logo", "purchase decision", "MSME". The analysis technique used is content analysis to identify patterns, themes, and relationships between halal logos, Muslim consumer perceptions, and purchase decisions. The result of this study is that the halal logo plays a significant role in increasing consumer trust, loyalty, and preference for MSME products. In addition, the use of halal logos is also considered an effective strategy in strengthening MSME branding. This research makes a theoretical contribution to the development of a sharia-based economy and provides practical insights for MSME actors in optimizing the potential of the halal market